Information System For Multi-Region LPG 3 Kg Realization Data Processing at PT Indung Tulot Energy (Pertamina) Banda Aceh - Ferri, M.; Ikhbar, Samsul; Munawir (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
This research aims to address challenges in the management and distribution activities of 3 Kg LPG at PT Indung Tulot Energy (Pertamina) Banda Aceh. These challenges include difficulties in data collection, distribution transactions, and efficient report generation. Data collection methods used were Field Studies and Literature Studies. The research resulted in an LPG 3 Kg allocation information system application, designed to accelerate and simplify allocation data management processes, sub-distributor data management, and improve reporting effectiveness. The system is intended to resolve existing problems and enhance services at PT Indung Tulot Energy (Pertamina) Banda Aceh